2009
DOI: 10.1038/nrcardio.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Role for TNF in atherosclerosis? Lessons from autoimmune disease

Abstract: Inflammatory pathways have been implicated in the initiation and progression of cardiovascular diseases. Accelerated atherosclerosis has been described in patients with chronic inflammatory diseases, particularly rheumatoid arthritis, disproportionate to individuals' detectable traditional vascular risk factors. This finding suggests that other pathways associated with inflammation might account for increased vascular risk in such diseases. Highly specific biologic agents can precisely block the activity of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
172
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(187 citation statements)
references
References 65 publications
5
172
0
10
Order By: Relevance
“…Recent results have indicated that the regulation of MMPs in response to TNF-α is involved in NF-κB activation in VSMCs (28,29). Consistent with previous studies, we demonstrated that TNF-α activates NF-κB in RASMCs, suggesting that the upregulation of MMP expression in response to TNF-α is mediated by this transcriptional factor.…”
Section: Discussionsupporting
confidence: 81%
“…Recent results have indicated that the regulation of MMPs in response to TNF-α is involved in NF-κB activation in VSMCs (28,29). Consistent with previous studies, we demonstrated that TNF-α activates NF-κB in RASMCs, suggesting that the upregulation of MMP expression in response to TNF-α is mediated by this transcriptional factor.…”
Section: Discussionsupporting
confidence: 81%
“…CD137 is expressed by various immune cells, such as activated CD4+ and CD8+ T lymphocytes, natural killer (NK) cells, CD4+CD25+ regulatory T cells (Treg), monocytes, neutrophils, mast cells, eosinophils, and dendritic cells9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 as well as nonimmune cells such as endothelial cells and vascular smooth muscle cells 10. The ligand of CD137 (CD137L) is primarily expressed on antigen‐presenting cells (dendritic cells, monocytes/macrophages, and B cells), human primary T cells22 and cardiac myocytes in myocarditis and aortic tissue in arteritis 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α and CD40 ligand (CD40L) have been found to play important roles in atherogenesis by provoking immune responses such as the release of proinflammatory cytokines, MMP activation, and oxLDL‐induced TF expression 7, 8, 9. In addition, increased expression of another TNFSF member, CD137 (4‐1BB, TNFRSF9), has been reported on T cells in human atherosclerotic plaques and the endothelium, and it is able to induce adhesion molecule expression in the endothelium and reduce smooth muscle cell proliferation upon activation by CD137 ligands (CD137L, 4‐1BBL, TNFSF9) 10.…”
mentioning
confidence: 99%
“…The TNF -mediated vascular dysfunction involves alterations in EC metabolism and function, platelet aggregation, ECblood cell interaction, VSMC function and proliferation (McKellar et al, 2009). It increases the expression of many pro-inflammatory, pro-coagulant, proliferative and pro-apoptotic genes involved in initiation and progression of atherosclerosis (Bergh et al, 2009).…”
Section: Tumor Necrosis Factor αmentioning
confidence: 99%